(untitled) (European Bison Conservation Newsletter, 2009)
The Demodecidae are one of the most specialized parasitic arthropods of mammals, so far recorded in representatives of thirteen mammalian order, therein 16 species were described from hoofed mammals. Parasitic adaptations involve size and shape of the body which is elongated, worm-like, providing a specific adaptation to life in hair follicles or in various glands and their ducts. In addition, demodecids show an extreme reduction of a number of morphological characters. Some species show, moreover, certain other, specific adaptations to various microhabitats; those adaptations may, for instance, involve, the shape and size of tagms, the shape and localisation of supracoxal spines, setae on the palps, claws or the presence of the dorsal process on the opisthosoma. Specific modifications have enabled particular species to adapt not just to life in the skin of different mammalian species, but also to the different microhabitats they have colonised there. As a result, particular host species are parasitised by synhospitalic species specific to them, usually differing in their location in the skin.